THE INFLUENCE OF DIGITAL MARKETING ON SALES RESULTS OF TRADITIONAL TRADERS AT HORAS TAX PEMATANGSIANTAR CITY - Desi Sistiani; Amelia Oktavia Sidauruk; Hendri Mayanta Tarigan (International Conference on Health Science, Green Economics, Educational Review and Technology, 2020)
Objective from study This is For know is There is the influence of digital marketing on results sale trader traditional in Pematangsiantar horas tax . Method research used _ is approach quantitative with questionnaires and manage data using SPSS. Results analysis regression linear simple showing that influential digital marketing variables positive and significant to results sales .